A Catalytic Cross‐Olefination of Diazo Compounds with Sulfoxonium Ylides. Issue 49 (8th November 2018) - Neuhaus, James D.; Bauer, Adriano; Pinto, Alexandre; Maulide, Nuno
Abstract: A ruthenium‐catalysed cross‐olefination of diazo compounds and sulfoxonium ylides is presented. Our reaction design exploits the intrinsic difference in reactivity of diazo compounds and sulfoxonium ylides as both carbene precursors and nucleophiles, which results in a highly selective reaction. Abstract : Similar, yet so different : A ruthenium‐catalysed cross‐olefination of diazo compounds and sulfoxonium ylides is presented. The reaction design exploits the intrinsic difference in reactivity of diazo compounds and sulfoxonium ylides as both carbene precursors and nucleophiles, which results in a highly selective transformation.